Smart Management in Islamic Education: AI-Driven Decision-Making and Institutional Performance - Yeni Tri Nur Rahmawati (JUMPA : Jurnal Manajemen Pendidikan, 2025)
This study examines how lecturer career development is implemented within an institutional context, with a particular focus on how academic practices are shaped through the interaction between formal policies and everyday activities. Using a qualitative case study approach, the research was conducted at UIN Maulana Malik Ibrahim Malang, involving faculty leaders, heads of study programs, and lecturers as key informants. Data were collected through in-depth interviews, participant observation, and document analysis, and were analyzed using an interactive model to identify patterns and relationships across different aspects of academic work. The findings show that lecturer career development is not carried out as a single, structured program, but rather emerges through interconnected academic activities, including pedagogical development, research engagement, scientific publication, academic collaboration, and community service. These activities are supported by institutional systems, yet their implementation varies depending on workload, institutional routines, and field conditions. In particular, the integration of research into teaching and the practice of community service demonstrate how formal programs are adapted in real settings. The study highlights that lecturer career development is shaped not only by institutional design but also by how lecturers interpret and carry out their roles in practice. This suggests the need for more adaptive and context-sensitive approaches in managing academic human resources, particularly within Islamic higher education. The findings contribute to a more grounded understanding of lecturer development as a dynamic and practice-based process.